Dentists' restorative decision‐making and implications for an 'amalgamless' profession. Part 1: a review. (17th September 2014) - Alexander, G; Hopcraft, MS; Tyas, MJ; Wong, RHK
Abstract The Minamata Convention has agreed to a worldwide reduction and ultimate elimination in the production and use of mercury containing products. This will have implications for the practice of dentistry. Australian organizations' pronouncements on the issue are limited and research examining the Australian context dated. The restoration of teeth with direct materials has changed significantly since the 1980s. Up to this time amalgam was the material of choice for direct posterior restorations. Its properties and guidelines for placement were, and remain, well established. Resin composite has replaced amalgam as the material of choice in many clinical situations. Despite inherent clinical disadvantages compared to amalgam, there continues to be a shift toward greater use of resin composite. There is consensus worldwide that the restoration of posterior teeth using resin composite now exceeds that of amalgam. The reasons for this are reviewed in this article along with current evidence and commentary relating to direct restorative and evidence‐based decision‐making, minimally invasive approaches, and approaches to education. The implications for these in an 'amalgamless' profession are identified.